2007
DOI: 10.1111/j.1471-4159.2007.05155.x
|View full text |Cite
|
Sign up to set email alerts
|

The newly synthesized pool of dopamine determines the severity of methamphetamine‐induced neurotoxicity

Abstract: The neurotransmitter dopamine (DA) has long been implicated as a participant in the neurotoxicity caused by methamphetamine (METH), yet, its mechanism of action in this regard is not fully understood. Treatment of mice with the tyrosine hydroxylase (TH) inhibitor α‐methyl‐p‐tyrosine (AMPT) lowers striatal cytoplasmic DA content by 55% and completely protects against METH‐induced damage to DA nerve terminals. Reserpine, by disrupting vesicle amine storage, depletes striatal DA by more than 95% and accentuates M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 53 publications
6
127
3
Order By: Relevance
“…Alternatively, MEPH has lessened potency at the DAT compared with METH, owing to the presence of the b-keto group negatively impacting the binding affinity of these compounds for the neurotransmitter transporters, and thus requiring higher doses to elicit transmitter release (Simmler et al, 2013). As this excessive DA release is thought to contribute to the toxicity of METH by increasing the amount of oxidative stress and free radicals through DA metabolism, promoting persistent inflammatory activation and eventual synaptic damage (Thomas et al, 2008), it was important to investigate the other DA-dependent behavioral and physiologic effects of these drugs, such as body temperature and locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, MEPH has lessened potency at the DAT compared with METH, owing to the presence of the b-keto group negatively impacting the binding affinity of these compounds for the neurotransmitter transporters, and thus requiring higher doses to elicit transmitter release (Simmler et al, 2013). As this excessive DA release is thought to contribute to the toxicity of METH by increasing the amount of oxidative stress and free radicals through DA metabolism, promoting persistent inflammatory activation and eventual synaptic damage (Thomas et al, 2008), it was important to investigate the other DA-dependent behavioral and physiologic effects of these drugs, such as body temperature and locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this conclusion, although there are no studies on 4MM release, an in vitro study found the magnitude of DA release mediated by MeCa to be similar to METH, and greater than that of MEPH (Simmler et al, 2013). Consequently, a greater release in DA would promote the hypothesis that MeCa would induce greater neurotoxicity than MEPH and/or 4MM, since it has been shown in multiple studies that increasing the amount of DA available for release enhances METH toxicity (Kita et al, 1995, Thomas et al, 2008, 2009). Indeed, the depletion levels reported above support this hypothesis.…”
Section: Neurotoxicity Of 4-methylmethamphetamine and Methcathinonementioning
confidence: 97%
“…One proposed mechanism is related to the dramatic increase in dopamine levels in the cytosol, resulting in oxidative stress (Cubells et al 1994;Fumagalli et al 1999;Guillot et al 2008). Supporting this view are studies that show depleting intracellular dopamine with reserpine and a-methyl-p-tyrosine reduces (Gibb and Kogan 1979;Schmidt et al 1985), and those that replenish dopamine, such as L-dopa, reproduce (Gibb and Kogan 1979;Thomas et al 2008) methamphetamine toxicity. On the other hand, hyperthermia induced by methamphetamine has been suggested to be the culprit of its neurotoxicity.…”
Section: Amphetaminesmentioning
confidence: 99%
“…monoaminergic deficits caused by METH. For example, pretreatment with the VMAT2 inhibitor reserpine worsens the dopaminergic deficits caused by METH (Wagner et al, 1983;Thomas et al, 2008). In addition, heterozygous VMAT2 knockout mice exhibit increased METH-induced dopaminergic deficits (Fumagalli et al, 1999).…”
Section: Figmentioning
confidence: 99%
“…A reduction in VMAT2 function/protein would promote this oxidative stress, because less DA would be sequestered. Indeed, reduced vesicular DA sequestration exacerbates METH-induced dopaminergic deficits (Wagner et al, 1983;Fumagalli et al, 1999;Guillot et al, 2008b;Thomas et al, 2008).…”
Section: Figmentioning
confidence: 99%